High doses of a national preschool program are associated with the long-term mitigation of adverse outcomes in cognitive development and life satisfaction among children who experience early stunting: a multi-site longitudinal study in Vietnam - Robinson, J. A.; Dinh, Phuong Thi Thu (Frontiers in Public Health, 2023)
Background: Stunting (low height-for-age) is a marker of cumulative developmental disadvantage that can also contribute to impaired cognitive development and poor psychological wellbeing. Several interventions designed to preserve stunted children's developmental potential through increasing their cognitive stimulation have proven to be effective. However, their resource-intensive nature limits their sustainability and scalability in the low-and middle-income countries in which 98% of stunted children live. The current study had three aims: to identify the domains of developmental disadvantage associated with stunting at 5 years of age in the Vietnamese context: to examine the relationship between Vietnamese children's stunting status at 5 years of age, the dose of the national preschool program they received, and their cognitive skills and psychological well-being at 4 ages; and to determine whether some doses of the national preschool program were associated with the mitigation of adverse cognitive and wellbeing outcomes among stunted children.The Young Lives Study in Vietnam (n = 2,000; 31 sites) provided archival data that allowed calculation of the approximate dose (in hours) of the preschool program received by children, and longitudinal data on children's growth (1, 5, 8, 12 and 15 years), receptive vocabulary (5, 8, 12 and 15 years), reading skills, mathematics skills and life satisfaction (each at 8, 12 and 15 years). Results: Stunting at 5 years of age was associated with diverse aspects of financial and social capital, greater exposure to health risks, lower preventive health care, and constraints on maternal care. Scores for all cognitive variables at all ages were positively associated with preschool dose and negatively associated with stunted growth at 5 years of age. That is, effects associated stunting and preschool dose at 5 years of age continued to be found during the subsequent 10 years. High doses of preschool education (3,000 hours or more) were associated with the mitigation of adverse outcomes for most cognitive variables at most ages.The current findings raise the possibility that generic preschool programs delivered at high dose may provide a scalable and sustainable intervention to support the life opportunities of children who experience early stunting.